Enhanced mechanical properties of biodegradable poly(butylene adipate-co-terephthalate) through naphthalate incorporation - Van Anh Thi Nguyen; Sun-Ho Jang; Yebom Kim; Yong-Seok Choi; Sung-Kon Kim; Seongseop Kim; Jun Woo Jeon (Polymer Testing, 2025)
Poly(butylene adipate-co-terephthalate) (PBAT) serves as a viable substitute for low-density polyethylene (LDPE), particularly in agricultural films and packaging. However, for broader application of PBAT, extensive research has been conducted to fundamentally enhance its mechanical properties. This study introduces a novel PBAT copolymer that incorporates naphthalate content to enhance mechanical performance by partially replacing terephthalate content with rigid aromatic naphthalate content. Synthesized via a two-step melt polymerization method with varying dimethyl 2,6-naphthalenedicarboxylate (DMN) content (0–100 mol% relative to the total phthalate content), the copolymer demonstrated a significant increase in tensile strength, reaching 56.01 MPa for PBATN80, compared to 14.43 MPa for pure PBAT, while maintaining elongation at break between 530 % and 743 %. X-ray diffraction analysis revealed that the crystalline structure of the copolymers changed in response to increasing naphthalate content; specifically, samples with naphthalate content exceeding 50 mol% exhibited distinct peaks associated with poly(butylene-2,6-naphthalate). This enhancement in their mechanical properties is believed to be attributed to the similarities in characteristics with poly(butylene naphthalate) (PBN). Importantly, biodegradability was preserved, albeit at slightly reduced rates. This research highlights a promising strategy to enhance mechanical properties of PBAT without compromising its biodegradable nature, suggesting its potential for sustainable applications.